Pengaruh Pembelajaran Daring Terhadap Hasil Belajar Bahasa Arab Kelas VIII SMPIT Permata Bunda Bandar Lampung - Rizki Fatmala; Muhammad Irham; Hamdal (Al Mitsali, 2022)
Since the COVID-19 pandemic, online learning is nolonger an option, but online is an obligation. Onlinelearning is the only option to ensure learning goes on.This certainly adds new challenges for every educationactor in Indonesia. The purpose of this study was todetermine whether or not online learning had an effecton Arabic learning outcomes at SMP IT Permata Bundaclass VIII Bandar Lampung in the 2020/2021 schoolyear.This research method uses quantitative research, theinstrument used in the form of questionnaires andpopulation documentation in this study is class VIIISMP IT Permata Bunda Bandar Lampung number 55, asfor the results of research that has been carried out byresearchers after conducting a normality test, thenresearchers conducted a linearity test to find out the data.is linear and can be used, then the researchers tested atthe final stage, namely a simple linear regression test,namely to find out the results of the study, it can be seenthat the value of tcount < ttable (0.-948 < 0.200) and thesignificance value is obtained 0.347 which means thevalue is more greater than 0.05, it can be seen that if thesignificance value > 0.05 means that the x variable hasno effect on the y variable, so it can be concluded that:There is no effect of online learning on Arabic learningoutcomes at SMP IT Permata Bunda Bandar Lampungwith a t value smaller than table meaning yes onlinelearning at SMP IT Permata Bunda Bandar Lampung isquite effective, and other factors that affect studentlearning outcomes such as: physical, psychological,family and so on.